Reversible Cerebral Vasoconstriction Syndrome Following Blood Transfusion in a Patient With Chronic Anemia: A Case Report - Amogh Verma; Govind Sharma; Ajeet Singh; Harshit Gupta; Deependra Pratap Singh; Abhay M. Gaidhane; Mahalaqua Nazli Khatib; Ganesh Bushi; Sanjit Sah; Rodrigue Ndabashinze (Clinical Case Reports)
ABSTRACT Reversible cerebral vasoconstriction syndrome (RCVS) is a rare neurological disorder characterized by transient constriction and dilation of cerebral arteries, leading to severe headaches and neurological deficits. This case report describes a 41‐year‐old woman with chronic anemia, acute chronic kidney disease, type 2 diabetes mellitus, and rheumatoid arthritis who developed RCVS following transfusion of packed red blood cells (PRBCs). She experienced sudden‐onset seizures and a thunderclap headache 5 days post‐transfusion. Diagnostic imaging, including computed tomography (CT) and magnetic resonance imaging (MRI), revealed the characteristic features of vasogenic edema. The patient was treated with blood pressure control and symptomatic relief for pain, resulting in gradual improvement. This case highlights the importance of recognizing RCVS as a potential complication of blood transfusions, particularly in patients with significant comorbidities. Understanding the possible mechanisms, including rapid hemoglobin correction, and the effects of residual plasma and storage lesions in transfused blood, is essential to prevent and manage this rare but serious condition.